A Study on the Relative Performance of Different Coagulants and the Kinetics of COD in the Treatment of a Textile Bleaching and Dyeing Industrial Wastewater - Wilheliza A. Baraoidan; Lin Lin Tun; Pag-asa D Gaspillo; Masaaki Suzuki (ASEAN Journal of Chemical Engineering, 2007)
Untreated wastewater from textile industries when discharged to nearby waterways would cause considerable health concerns to humans and animal life and to the host environment. They contain various chemicals such as dyes, detergents and surfactants, some of which are recalcitrant to biodegradation. Such wastewater can be better remediated by chemical treatment. The treatment of a textile bleaching and dyeing industrial wastewater was done by Coagulation and Flocculation Method using a jar test apparatus. Alum, polyaluminum chloride (PAC), and ferrous sulfate were used in separate runs as coagulants, while excelfloc 264 (a polyacrylamide copolymer) was used as flocculant. Preliminary tests were first conducted to determine the appropriate coagulation and flocculation agitation rates and settling time. The initial pH of the sample effluent was varied from 5 to 8 for alum coagulation, 5 to 8.5 for PAC coagulation and 9 to 11 for ferrous sulfate coagulation. The dosages of each coagulant and the excelfloc were varied from 200 to 1000 ppm, and 0.5 to 2.5 ppm, respectively. Experimental results showed that the optimum initial pH of the wastewater using alum, PAC, and ferrous sulfate were 7, 7.5, and 10, respectively. The optimum dosages of the coagulants were found to be 600ppm for alum and 800ppm for both PAC, and ferrous sulfate. The optimum flocculant dosages were 1.5ppm with alum, 1 ppm with PAC and 2ppm with ferrous sulfate. The highest percentage removal of COD, Total Suspended Solids (TSS), Total Dissolved Solids (TDS), chromium, and color were found to be 58.55%, 65%, 36.51%, 76.45%, and 78.96%, respectively, using alum: 65.4%, 67.5%, 35.84%, 44.92%, and 75.49%, respectively using PAC; and, 55.72%, 34.16%, 33.95%, 19.88%, and 48.56%, respectively, using ferrous sulfate. Among the three coagulants tried, coagulation with PAC gave the highest percentage of COD removal of 65.64% and TSS removal of 67.5% while alum gave the highest removal of both chromium and color at 76.45% and 94.49%, respectively. Rapid and slow agitation rates used were 240rpm for 1 minute and 40rpm for 20 minutes, respectively; while settling time was 30 minutes. Kinetics of the COD removal was studied at the optimum conditions. Kinetic model, determined by curve fitting with the coagulation/flocculation reaction, was observed to follow a first-order rate of reaction.